Environmental Innovation and Financial Performance: The Moderating Role of Environmental Performance in Indonesian Firms - Anam, Khoirul; Apriliyanto, Nanang; Wibowo, Wahyu Adi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the effect of environmental innovation on financial performance, with environmental performance acting as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange during the 2019–2021 period. The research adopts a quantitative approach using secondary data derived from annual reports and financial statements. A purposive sampling technique is applied, resulting in a final sample of 57 companies that meet the specified criteria, including participation in PROPER and ESG disclosure. The data are analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS. The empirical findings indicate that environmental innovation has a positive and statistically significant effect on financial performance (β = 0.247; p = 0.040), suggesting that firms engaging in environmentally oriented innovation tend to achieve better profitability through improved efficiency and resource utilization. In contrast, environmental performance does not show a significant direct effect on financial performance (β = -0.190; p = 0.086), implying that higher environmental compliance alone may not immediately translate into financial gains. Furthermore, the moderating analysis reveals that environmental performance significantly weakens the relationship between environmental innovation and financial performance (β = -0.273; p = 0.030). This negative moderating effect indicates a potential trade-off, where higher environmental performance introduces additional costs and operational constraints that reduce the financial benefits of innovation. Overall, the study highlights the importance for firms to strategically balance environmental initiatives with financial efficiency to achieve sustainable performance.